Weight lifting for sports specific benefits - Brewer, C.; Favre, M.; Low, L. (coachesinfo.com, 2008)
Top-level sports performance is based upon the need to develop power (the product of force x velocity). The basis for power generation in many sporting contexts is the stretch-shortening cycle (or plyometric response). In order to train the recruitment of maximum numbers of motor units (a motor unit is a motor nerve and all of the fibres innovated by that nerve), multi-joint, multi-muscle exercises that allow maximum force generation in minimal time have formed the cornerstone of training exercises for sports performers. The snatch and clean weightlifting movements and derivatives of these exercises, are the major resistance training exercises for developing power in sports performers. If there is to be an effective transfer of training effect between sports performance and training action, these movements need to facilitate a plyometric action: This can be done if the strength and conditioning coach teaches his/ her athletes to perform a double-knee bend (DKB) action within the training movement for both the snatch and clean lifts. The DKB allows a greater force to be transmitted more effectively, greater transfer of training effects to other sports and also it is a safer lift with less potential risk to the back.